Abdominoplasty: An Easy Approach to Giant Abdominal Lipomas - Bayan Alsharif; Hatan Mortada; Aeshah Mandili; Fahad Aljindan (Case Reports in Surgery)
Introduction. Giant lipomas, which are greater than 10 cm, are rare, cosmetically unacceptable, and deteriorate the quality of daily living. Removal of giant abdominal lipomas either by liposuction, excision, or both, can lead to the formation of a loose, pendulous drooping abdomen, and abdominal wall laxity, which is aesthetically displeasing. The objective of this case report is to highlight an easy approach to treat giant abdominal lipoma through therapeutic abdominoplasty. Case History. In this case, a 29-year-old man with a known case of hypothyroidism and HCV was in remission but had a huge abdominal mass on his lower left side; it progressed for 7 years and increased in size and caused discomfort. His BMI was 29.53 and the mass measured about 15×13 cm. All other investigations were normal and showed no malignancies. He underwent excision of the giant abdominal lipoma using a standard abdominoplasty approach. Conclusion. In conclusion, in selected patients, giant abdominal lipomas can be successfully excised along with the redundant abdominal skin.